2018
DOI: 10.1093/toxsci/kfy106
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Metabolism in the Progression of Human Nonalcoholic Steatohepatitis

Abstract: Alcohol metabolism is a well-characterized biological process that is dominated by the alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) families. Nonalcoholic steatohepatitis (NASH) is the advanced inflammatory stage of nonalcoholic fatty liver disease (NAFLD) and is known to alter the metabolism and disposition of numerous drugs. The purpose of this study was to investigate the alterations in alcohol metabolism processes in response to human NASH progression. Expression and function of ADHs, ALDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…3b). Ethanol-treated Liver-Chips also exhibited significant changes in the expression of members of the alcohol dehydrogenase (ADH) gene family, including ADH1C 48 , ADH1B 49 and ADH1A, all involved in alcohol metabolism 49 .Most importantly, , we found that alcohol induced the expression of CYP2E1, critical for ethanol oxidation and the associated induction in oxidative stress (Fig. 3c).…”
Section: Ethanol-induced Steatosis In the Liver-chipmentioning
confidence: 73%
“…3b). Ethanol-treated Liver-Chips also exhibited significant changes in the expression of members of the alcohol dehydrogenase (ADH) gene family, including ADH1C 48 , ADH1B 49 and ADH1A, all involved in alcohol metabolism 49 .Most importantly, , we found that alcohol induced the expression of CYP2E1, critical for ethanol oxidation and the associated induction in oxidative stress (Fig. 3c).…”
Section: Ethanol-induced Steatosis In the Liver-chipmentioning
confidence: 73%
“…The knockout of Pla2 has been proven to achieve a 56.5% decrease in fatty acid influx in hepatocytes . The administration of YZH liquid also increases the expression of alcohol dehydrogenase, the impairment of which has been noticed in the liver tissue of NASH patients . Overall, YZH liquid reduces hepatic lipid accumulation in HFHCD‐fed NASH rats by limiting lipogenesis and accelerating β‐oxidation.…”
Section: Discussionmentioning
confidence: 97%
“…Nonalcoholic fatty liver disease (NAFLD) is the most frequent chronic liver disease; alcohol dehydrogenase and aldehyde dehydrogenase collectively showed altered expression and function in the progression of nonalcoholic steatohepatitis (NASH) patients, which may also lead to significant alterations in the pharmacokinetics of substrate drugs. This information could be useful in making appropriate dosing adjustments for NAFLD patients taking drugs that are metabolized by these pathways [25].…”
Section: Discussionmentioning
confidence: 99%